Density-dependent reproductive and vegetative allocation in the aquatic plant Pistia stratiotes (Araceae) - Freitas Coelho, Flávia (2005)
Pistia stratiotes is an aquatic macrophyte that grows in temporary-ponds in the southern Pantanal, Brazil. It reproduces both sexually and asexually and is usually observed forming dense mats on the water surface, a condition favored by the plant’s vegetative reproduction coupled with an ability for rapid growth. In this study we examined the effect of densely crowded conditions on the production of reproductive and vegetative structures. In addition, we verified whether there is a trade-off between clonal growth and investment in sexual reproductive structures, and whether there is an allocation pattern with plant size. Individual plant biomass and the number of the rosettes producing sexual reproductive structures and vegetative growth structures both increased with density. Increase in plant size resulted in increased proportional allocation to sexual reproductive structures and vegetative growth structures. Allocation of biomass to reproduction did not occur at the expense of clonal growth. Thus, the density response appears as a increase of rosettes producing sexual reproductive structures and vegetative growth structures. Therefore, long leaves and stolons may be adaptive under densely crowded conditions where competition for light is intense. An important aspect in the study of trade-offs is the size-dependency of the allocation patterns .Usually, larger plants produce more biomass. Therefore, larger plants can allocate more biomass to both vegetative and sexual reproduction than smaller plants and thus show a positive correlation between both traits rather than the expected negative one.